Dynamic Mechanical Property Experiment of Viscous Material for Viscous Damping Wall - Sun, Feifei; Yang, Jiaqi; Wu, Tanye (Frontiers in Materials, 2019)
Viscous damping wall (VDW) is an effective velocity-dependent damper, which can dissipate earthquake energy by shear strain of viscous material. The damping force equation of VDW can only be obtained from regression of VDW dynamic test results, as velocity exponent of power-law material can not be obtained from rheometers. This study designed a Dynamic Sandwich-Type Shear (DSTS) test which matches the engineering working condition of VDW, and conducted a series of experiments with different frequencies and strain amplitudes. Simple data procession methods were proposed to calculate velocity exponent and storage/loss modulus of polymer from experimental data. Comparison with methods adapted from those for VDW formula validated that radial linear regression method was proper to separate stress components and pivotal point method was accurate to evaluate velocity exponent. The velocity exponents obtained varied from 0.8 to 1, with various loading frequency and strain amplitude. Finally, the differences between the results of storage/loss modulus in DSTS test and ARES test were compared. Due to the extrusion effect caused by engineering working condition, the storage and loss modulus obtained by DSTS test was larger than the modulus obtained by ARES test.